Meningkatkan Aktivitas dan Keterampilan Berpikir Kritis Muatan IPA Menggunakan Model BASAMAAN di Kelas V SDN Sungai Miai 8 - Rahmida, Riska Auliya; Agusta, Akhmad Riandy (Peneliti.net, 2025)
The problem of this study is the low level of critical thinking and activity of students, as well as their learning outcomes in the science subject of SDN Sungai Miai 8 in grade V students. By using the BASAMAAN model, this problem is sought to be solved. This study aims to test how students' learning outcomes, critical thinking skills, and activity levels increase when they are involved in science learning using the BASAMAAN learning model. This research uses Classroom Action Research (PTK), which was conducted during 4 meetings. Grade V students of SDN Sungai Miai 8 Banjarmasin totaling 25 students, consisting of 11 female students and 14 male students are the focus of this research. Quantitative data on student learning outcomes received through individual written exams are combined with qualitative data collected through observation of teacher activities, student activities, and students' critical thinking skills. The findings of the study showed that the teacher's performance at the first meeting received a score of 39, and that this result consistently rose until the last meeting the score reached 52. With a percentage of 40% in the activity section of meeting 1, students who met the criteria showed a high level of activity. This trend lasted until the last meeting, when the proportion reached 84%. In meeting 1, the percentage of students who met the criteria for critical thinking ability was 32%. These results continued to increase until the last meeting, when the percentage of students who met the criteria was 80%. The application of the BASAMAAN model can improve student activities, critical thinking skills, and learning outcomes, according to the findings of the study.